Effects of photoperiod on Growth and Yield of Flowering Chinese Cabbage (Brassica rapa var. parachinensis.) - CHATHAOKALOR1, Daovang; LAO, Ye; SITHIVOHAN, Insavai; DAOVONGDEUAN, Siphanh; PHOMLASABOUD, Khantavanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
The study on effects of photoperiod on growth and yield of flowering Chinese cabbage, had three main objectives as 1) to investigate the photoperiod responding the yield of flowering Chinese cabbage, 2) to compare the harvesting times of flowering Chinese cabbage and, 3) to find out a good relationship between photoperiod and temperature on the productivity. The design was conducted by Completely Randomized Design (CRD) with 3 Replications and 4 Treatments: T1 = Sunlight (Control), T2 = 18 hours per day (Sunlight + CFL bulb from 6:00-12:00 PM), T3 = 18 hours per day (Sunlight + CFL bulb from 0:00-6:00 AM), T4 = 24 hours (Sunlight + CFL bulb 12 hours). The space between a plant was 20x20 cm in distance and the size of plantbed was 1x1 m, with 15.6 m2 in total area. A CFL bulb per bed was set and 80 cm in height was determined. The composition of yield as height, number of leaves, width of leaves, length of leaves, weight (gram per plant) were collected. The program of statistix 8.0 and Microsoft Excel were used for data analysis. This experiment was conducted at Souphanouvong University, with more than a month in time duration, from 03/2-20/3/2019. Effects of different photoperiods resulted the composition of yield and yield results had statistical significant differences at 95%. The numbers of leaves were 8.30, 8.30, 8.05 and 7.35 leaves, heights were 37.75, 35.70, 34.75 and 27.45 cm, width of leaves showed 10.66, 10.59, 10.46 and 7.80 cm, and Length of leaves were 15.19, 14.82, 14.68 and 12.17 cm. The results of experiment clearly shown that, offering 24 hours of photoperiod was the maximization on growth and yield of flowering Chinese cabbage as the highest yield, and then 18 hours per day (Sunlight + CFL Bulb from 0:00-6:00 AM), 18 hours per day (Sunlight + CFL Bulb from 6:00-12:00 PM) and Sunlight were 62.98, 62.31, 56.94 and 33.41 g/plant, respectively. The relationship between photoperiod and temperature for yield indicated the relationship between photoperiod and yield of flowering Chinese cabbage with value of R2 was 0.76 and the yield was increased when temperature decreased,whereas the harvesting times had no statistical significance.